O papel do fomentar no processo de estruturação industrial em Goiás (1984 - 1999) - Paschoal, Júlio Alfredo Rosa (2001)
In our study, we studied the Participation and Promotion Fund Industrialization of the State of Goiás - FOMENTAR, which was a program to attract industries used by the State in the period between 1984 and 1999. The program's priority was to strengthen agro-industry, which would be implemented through technical and financial support to micro, small, medium and large undertakings, provided they are considered "high relevance" for the socio-economic development of the State of Goiás. The alleged objectives for the implementation of the program related to the attraction of industries and the promoting a process of spatial deconcentration of wealth in the State, generating strong impacts on employment. Furthermore, the idea defended was that the program would not be acting in the tax waiver, but in offering "credit" to the beneficiaries of the Fund. Our work aims to study the implementation of this program and its impacts. The hypothesis that the program was limited by two issues stands out: a) the logic of Brazilian regional devolution concentrates a space of diversification limited to industries that are outside the industrial polygon, as the attraction of industries through tax waiver is not able to reverse this issue bigger; b) there were distortions in the implementation of the program. As for the first question, we will not go into it further in this work, as it it should serve as a background for our dissertation. In chapter I we indicate which is the perspective adopted on this issue. It is noteworthy that this is a introductory chapter to the questions that we will raise from the second chapter and that concern the adoption of an eminently regional program to attract industries, disconnected from a broader industrial policy. Given this, perspective, this introduction is extremely succinct, and the opening chapter justifies the studied theme and locates it in time, associating it with the debates on regional deconcentration of wealth, also highlighting what was the insertion logic of the State of Goiás in this process.The second issue that will be focused on will be at the heart of our work, which more internal analysis of the Program. Our hypothesis is that the Fomentar Program worked since its inception, using tax waivers, and this logic was in-depth based on changes made during the course of its activities. In chapter ll, we will show that this was already implicit since the formation of the Program, since the non-collection of monetary restatement on the debt principal, led to tax exemption, since, in the period in which the concession was made, the inflation was rising. In this chapter we will deal with the analysis of the initial conformation of Program, in order to verify what, in fact, its objectives were and where it intended to arrive, with the granting of benefits, mainly in the tax area. We will analyze in detail the Program's legislation, the origin of the resources, the profile of the companies contemplated and the initial logic of the fiscal support granted, as a starting point the start of its operation. From then on, in chapter III, we will indicate which other misdirections presented by the program, namely: - the postponement of deadlines, for the enjoyment and payment of benefits, imposed by changes in legislation; - the non-accounting of part of the ICMS credits (generated in the period from 1986 to 1994) to the State, which contributed to reinforce our idea that the logic of program was effectively based on tax exemption; - the modification of the legislation, which made it impossible for smaller companies to access postage; - the adoption of the debt auction, after the end of inflation, which would explain the logic of tax waiver. From these distortions, we intend to highlight that the industrial attraction effect came about from a tax waiver of great magnitude and that, in the In fact, the attraction of the industries was based on the previous pattern, in a concentrated way, not including smaller companies and treating a small number of large companies in a privileged way.